由题意,得:f(-5,6))=(6,-5) 所以,原式=G(6,-5)=(-6,5)
若f(a,b)=(b,a),G(m,n)=(-m,-n)则G(f(-5,6)= (
1个回答
相关问题
-
f(a,b)=(a\1,b\1),g(m,n)=(-m,-n),求g(f(4,5))
-
(2012•六盘水)定义:f(a,b)=(b,a),g(m,n)=(-m,-n).例如f(2,3)=(3,2),g(-1
-
定义:f(a,b)=(b,a),g(m,n)=(﹣m,﹣n).例如f(2,3)=(3,2),g(﹣1,﹣4)=(1,4)
-
设集合M={a,b,c},N={0,1},若映射f:M→N满足f(a)+f(b)=f(c),则映射f:M→N的个数为__
-
设集合M={x|f(x)=0},N={x|g(x)=0},则方程f(x)•g(x)=0的解集是( ) A.M∩N B.
-
已知集合A=a,b,c,d,e B=m,n,f,g
-
函数的f(x)=(ax+b)/(cx+a) g(x)=(lx+m)/(nx+l) 且b:c=m:n 证明:f(g(x))
-
柯西中值定理证明:f(a)-f(m)/g(m)-g(b) =f'(m)/g'(m) f(x),g(x)满足在区间a,b连
-
A.若a^2=5a,则a=5 B.若m/b=n/b,则m=n 哪个正确,
-
若a÷b=7,a+b=9.6,则a=(),b=();若m+n=91,m÷n=8······1,则m=(),n=()